2015
DOI: 10.1016/j.electacta.2015.08.106
|View full text |Cite
|
Sign up to set email alerts
|

The Hydro-electro-thermal Performance of Air-cooled, Open-cathode Polymer Electrolyte Fuel Cells: Combined Localised Current Density, Temperature and Water Mapping

Abstract: In situ diagnostic techniques provide a means of understanding the internal workings of fuel cells so that improved designs and operating regimes can be identified. Here, a novel metrology approach is reported that combines current and temperature mapping with water visualisation using neutron radiography.The approach enables a hydro-electro-thermal performance map to be generated that is applied to an air-cooled, open-cathode polymer electrolyte fuel cell. This type of fuel cell exhibits a particularly intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 88 publications
3
29
0
Order By: Relevance
“…In air-cooled, open-cathode systems the temperature depends on the voltage and current density [67,78], air cooling flow rate [73,76], and heat transfer characteristics of the stack. In practice, the temperature management is normally performed using a single-point thermocouple inserted in the centre of the cell [18,29,75], or for development work using multiple microthermocouple measurements at various locations in the fuel cell [15,79,80].The authors have previously studied dead-ended operation, on a cell with dry fuel and air, using techniques such as mass spectrometry (revealing nitrogen 6 accumulation), thermal imaging and electrochemical impedance spectroscopy [29], as well as combined current and temperature mapping, revealing large gradients between the fuel inlet and exhaust [33].Here, we present the results obtained by applying the recently developed hydroelectro-thermal analysis [57] technique to an air-cooled, open-cathode fuel cell operated in dead-ended anode mode, to capture dynamic operation, combining current and temperature mapping with water mapping during dead-ended operation. …”
mentioning
confidence: 99%
“…In air-cooled, open-cathode systems the temperature depends on the voltage and current density [67,78], air cooling flow rate [73,76], and heat transfer characteristics of the stack. In practice, the temperature management is normally performed using a single-point thermocouple inserted in the centre of the cell [18,29,75], or for development work using multiple microthermocouple measurements at various locations in the fuel cell [15,79,80].The authors have previously studied dead-ended operation, on a cell with dry fuel and air, using techniques such as mass spectrometry (revealing nitrogen 6 accumulation), thermal imaging and electrochemical impedance spectroscopy [29], as well as combined current and temperature mapping, revealing large gradients between the fuel inlet and exhaust [33].Here, we present the results obtained by applying the recently developed hydroelectro-thermal analysis [57] technique to an air-cooled, open-cathode fuel cell operated in dead-ended anode mode, to capture dynamic operation, combining current and temperature mapping with water mapping during dead-ended operation. …”
mentioning
confidence: 99%
“…Using neutron radiography on similar cells, previous imaging work in the throughplane direction showed that the area under the cathode cooling channel lands has the greatest concentration of water [38]. However, as imaging was performed in the through-plane direction, no information was available regarding the distribution of water within the layers of the MEA.…”
Section: In-plane Water Distribution For Air Cooled Open Cathode Fuelmentioning
confidence: 99%
“…In the first case, it is possible to differentiate between the water content in the cathode and the anode GDL [29][30][31][32][33][34][35][36]. In the second case, it enables investigations of the effect of different designs, components, and operating conditions on the water distribution across the lateral extent of the cell [37][38][39][40][41][42][43][44][45][46][47]. Neutron imaging has been combined with other modelling and experimental techniques, such as current mapping [48], computational fluid dynamics (CFD) model validation [34,49,50], optical imaging [51], neutron scattering [52] and localised electrochemical impedance spectroscopy (EIS) [53].…”
Section: Water Visualisation In Fuel Cellsmentioning
confidence: 99%
See 2 more Smart Citations